2021
DOI: 10.3390/cells11010031
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 Receptor Is a Regulator of Morphine-Induced Plasticity in the Rat Dorsal Striatum

Abstract: Long-term exposition to morphine elicits structural and synaptic plasticity in reward-related regions of the brain, playing a critical role in addiction. However, morphine-induced neuroadaptations in the dorsal striatum have been poorly studied despite its key function in drug-related habit learning. Here, we show that prolonged treatment with morphine triggered the retraction of the dendritic arbor and the loss of dendritic spines in the dorsal striatal projection neurons (MSNs). In an attempt to extend previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Reportedly, therapy with morphine for at least three days results in substantial levels of morphine dependence [ 4 ]. Chronic morphine use promotes neurobiological adaptations, including synaptic and structural plasticity in specific brain regions, that ultimately lead to the development of addiction [ 5 , 6 ]. However, there is currently incomplete knowledge of the molecular mechanisms behind the transcriptional regulation of morphine addiction in the striatum, despite the tight association between this region and the establishment of drug-related habits and the consolidation of addiction [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, therapy with morphine for at least three days results in substantial levels of morphine dependence [ 4 ]. Chronic morphine use promotes neurobiological adaptations, including synaptic and structural plasticity in specific brain regions, that ultimately lead to the development of addiction [ 5 , 6 ]. However, there is currently incomplete knowledge of the molecular mechanisms behind the transcriptional regulation of morphine addiction in the striatum, despite the tight association between this region and the establishment of drug-related habits and the consolidation of addiction [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that drugs of abuse elicit glutamatergic synaptic plasticity that contributes to the reorganization of neural circuits, and putatively, the establishment of addictive behaviors ( van Huijstee and Mansvelder, 2014 ; Christian et al, 2021 ; Pascoli et al, 2022 ). Dopamine, which is released in response to nicotine exposure, is a prerequisite for drug-induced plasticity ( Belin et al, 2009 ; Lee et al, 2020 ; Rivera et al, 2021 ), and a key regulator of structural and synaptic plasticity ( Urakubo et al, 2020 ; Speranza et al, 2021 ). In addition, nicotine activates nicotinic acetylcholine receptors (nAChRs), which also has been demonstrated to be important for synaptic plasticity at both inhibitory and excitatory synapses ( Dani et al, 2001 ; Partridge et al, 2002 ; Adermark, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Each slice was transferred to a recording chamber that was perfused continuously with oxygenated ACSF at 32–34 °C following our standard protocol [ 45 , 46 ]. LC neurons were visualized using infrared gradient contrast video microscopy (Eclipse workstation, Nikon) and with a 60X water-immersion objective (Fluor 60X/1.00 W, Nikon).…”
Section: Methodsmentioning
confidence: 99%